Actuarial Evaluation of Pension Risks of Russia: from Theory to Practice - Kuklin, Aleksandr Anatolyevich; Shipitsyna, Svetlana Evgenyevna (Economy of Regions, 2017)
The article discusses the origins of the development of pension systems in the world, shows the causes of the emergence of various models of public pension provision. We pay a particular attention to the history of the formation of the Russian pension system, and analyse the stages and causes of modern reform. From the position of modern legislation, we systemise the forms, types of pension provision and pension insurance in the Russian Federation from the point of view of the sources of financing and subjects of pension relations. The authors have defined the concept of “actuarial evaluation” from the point of view of the process and system approach. We have revealed the content of the pension risk category, as well as classified the pension risks by the spheres of origin. The authors have developed the methodology of actuarial estimation of the risks of the pension system classified by different criteria: demographic, economic, financial, labor risks. The proposed methodological approach to the evaluation of pension risks is based on the comprehensive assessment of socio-economic indicators and the identification of dependencies between socio-demographic and economic processes in the pension system and economy of the country. The authors have tested the developed tools on the actuarial estimation of the pension risks of the Russian Federation. The article presents the results of calculations and identifies critical risks for the Russian pension system. We have proved that stagnation processes in the economy and a high share of the shadow economy represent the greatest threat to the Russian pension system in the short term, whereas, the aging of the population and the increase in life expectancy - in the long term.